Insight into the Local Atomic Structure Order and Luminescence of Rare Earths - Khan, Latif Ullah; Khan, Zahid Ullah; Umar, Muhammad Abdullah (The Nucleus, 2023)
The rare earth (III) complexes are remarkable photoemitters in visible to near-infrared spectral region, manifesting wide photonic applications in organic light-emitting diodes (OLEDs), telecommunications, optical lasers, display devices, optical quantum memories and medical diagnostics. In order to get detailed insight into the photo-physical characteristics of the luminescent rare earth complexes, it is very important to probe the local chemical environment/electronic structure of the trivalent rare earth ion sites. The X-ray absorption fine structure spectroscopy (XAFS) is very efficient to probe the RE3+ ions from oxidation state/electronic structure in the X-ray absorption near edge spectroscopy (XANES) range to the local atomic structure order around the photoabsorber in extended region (EXAFS). In this work, we explored the electronic and local atomic structure of the typical RE3+ β-diketonate complexes, [Eu(TTA)3(H2O)2] and [Gd(TTA)3(H2O)2], TTA: 3-thenoyltrifluoroacetonate by XANES, EXAFS fit and continuous Cauchy wavelet transform (CCWT) analyses. The optical properties are discussed based on the local structural evidences of RE3+ site obtained from the quantitative analysis of the XAFS data. The visualization of visible emission under irradiation with hard X-ray beam demonstrated that the [Eu(TTA)3(H2O)2] complex can be an efficient new generation X-ray organic scintillator.